Spatial Perception Enhancement in Assembly Training Using Augmented Volumetric Playback - Sasikumar, Prasanth; Chittajallu, Soumith; Raj, Navindd; Bai, Huidong; Billinghurst, Mark (Frontiers in Virtual Reality, 2021)
Conventional training and remote collaboration systems allow users to see each other’s faces, heightening the sense of presence while sharing content like videos or slideshows. However, these methods lack depth information and a free 3D perspective of the training content. This paper investigates the impact of volumetric playback in a Mixed Reality (MR) spatial training system. We describe the MR system in a mechanical assembly scenario that incorporates various instruction delivery cues. Building upon previous research, four spatial instruction cues were explored; “Annotation,” “Hand gestures,” “Avatar,” and “Volumetric playback.” Through two user studies that simulated a real-world mechanical assembly task, we found that the volumetric visual cue enhanced spatial perception in the tested MR training tasks, exhibiting increased co-presence and system usability while reducing mental workload and frustration. We also found that the given tasks required less effort and mental load when eye gaze was incorporated. Eye gaze on its own was not perceived to be very useful, but it helped to compliment the hand gesture cues. Finally, we discuss limitations, future work, and potential applications of our system.